1967
DOI: 10.1172/jci105645
|View full text |Cite
|
Sign up to set email alerts
|

Independence of Hydrogen Ion Secretion and Transport of Other Electrolytes in Turtle Bladder*

Abstract: Abstract. The relationship between hydrogen ion secretion and the transport of other electrloytes was examined in the isolated urinary bladder of the water turtle. Symmetrical solutions which were free from exogenous carbon dioxide and bicarbonate bathed the two surfaces of the preparation, and the spontaneous electrical potential of the bladder was nullified by a voltage clamp. Active transport of sodium from mucosal to serosal medium was confirmed by simultaneous bidirectional flux measurements and found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1967
1967
2007
2007

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(19 citation statements)
references
References 12 publications
3
16
0
Order By: Relevance
“…These results include values obtained with the mucosal pH being varied from 5 to 7.4. The equivalence of those two methods of measurements confirms the earlier findings of Steinmetz (30).…”
Section: Measurement Of the Rate Of H + Secretionsupporting
confidence: 88%
“…These results include values obtained with the mucosal pH being varied from 5 to 7.4. The equivalence of those two methods of measurements confirms the earlier findings of Steinmetz (30).…”
Section: Measurement Of the Rate Of H + Secretionsupporting
confidence: 88%
“…H' secretion and Na+ absorption, on the other hand, can be supported to an appreciable extent by anaerobic energy. Thus, Steinmetz, Omachi, and Frazier (9) observed that dinitrophenol failed to inhibit H+ secretion in their system in which exogenous C02 was absent. Similarly H' secretion was reduced only moderately' by deoxygenation carried out at a constant CO.…”
Section: Discussionmentioning
confidence: 94%
“…Hence, it must be coupled either directly to metabolic energy production or to the active transport of another ion such as Na+ or Cl-, a possibility examined in the following article (9).…”
Section: Discussionmentioning
confidence: 99%